Contribuições da lei n° 13.185/2015 para a prevenção do bullying: um estudo no Centro de Ensino Professor Antenor Bogéa em Matões do Norte - MA - SILVA, Vânia Pimentel (2024)
This research verified how to promote, from the teaching of Art and Sociology, preventive actions against the practice of bullying, considering Law no 13,185/2015, to prepare a Pedagogical Guidelines Booklet with didactic guidelines for teachers at the Professor Antenor Bogéa Teaching Center in municipality of Matões do Norte - MA. To achieve this objective, we analyzed the Maranhense Territory Curriculum Document (2022), the pedagogical political project (2022), annual content plans for Art and Sociology (2023), National Curricular Parameters – Art (2000), the Common National Curricular Base ( 2017), the National Education Guidelines and Base Law of No. 9393/96, the National Curricular Guidelines for Basic Education (2018), with the aim of ensuring actions to prevent bullying situations in this school. The construction of this dissertation text begins by discussing the federal, state and municipal legislation that addresses and supports the Program to Combat Systematic Intimidation (Bullying) throughout Brazilian territory. Next, he highlighted the composition of the Art curriculum, based on the framework based on Subtil (2012), Barbosa (2010; 2014; 2017), Gabriel; Martins (2020), Richter, (2012), while the Sociology curriculum was considered by researchers Machado (1987), Wieczorkievicz (2022), Caregnato; Cordeiro (2014), Jinkings (2007), Sarandy (2004), Lahire (2014), to assess the importance, contribution and how it develops at the Professor Antenor Bogéa Teaching Center, with a view to presenting curricular pedagogical strategies for the prevention of bullying. The data collection instruments were structured interviews, observations, documentary research and questionnaires. For data analysis and interpretation, we opted for graphical representation, based on the construction of tables and graphs. In this research process, we mainly used the studies of Fante (2005), Sousa (2021), Silva (2010), Caputi and Silva (2020), Pereira (2020), Alkimin and Nascimento (2010), Tessaro and Trevisol ( 2020), Minayo (2001), Gil (2011), Damiani (2012), Triviños (2006), Gressler (2003), among others.